Cinema as a Mirror of Urban Identity Crisis: Semiotics and Sustainability in ‘Dark City’ - Marjan Alikhanzadeh (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Identity is a foundational element of human civilization, shaping the meaning and sustainability of urban spaces. This study examines how evolving identities, influenced by modernism, impact urban sustainability, using the film Dark City as a case study. Modernism has extremely altered individual and collective identities, with these shifts evident in cultural mediums like cinema. Applying a semiotic analysis framework, the research analyzes sustainable place indicators to assess identity’s role in defining spaces. Findings indicate that modernism has eroded place identity, weakening urban sustainability in social, environmental, and cultural dimensions. The study concludes that sustaining meaningful urban environments requires preserving and revitalizing identity, positioning it as a critical factor in future urban development. By linking cinematic representation to real-world urban challenges, this research highlights the urgent need to reconcile modernity with place-based identity to foster resilient, sustainable cities.